Great Opportunity - Janeček, Vít (Czech Republic, 2011)
Labour agents promise locals in Mongolia a much better life if they move to the Czech Republic to work. Many are attracted by the idea. They sell their homes and travel the long distance west. However, what they find is not what they had been led to expect. They do manual labour in shifts of up to 14 hours and are left with little cash after expenses have been docked from their pay packets. Ignorance of Czech law and the language barrier lead to problems that can culminate in serious debts. The film director records the testimonies of several Mongolian families who have to contend with difficult working and living conditions.
Verzio Film Festival Submission
Keywords: Documentary films